The thing Lenny loves most about baseball - Larsen, Andrew, 1960- (Kids Can Press, 2021)
"Andrew Larsen evokes the eternal hope and joy of all true baseball fans --- along with their love of facts --- in this heartwarming story about a baseball-loving boy who doesn't give up.Lenny can't get enough of baseball. He loves to play. And he loves to pore over his Big Book of Baseball Facts. He wants to be in the big leagues someday, and, he figures, the more he knows, the better his chances. The only thing is, though he tries to keep his eye on the ball as it heads his way during a game, it somehow ends up by his feet. “You just need to practice,” his dad tells him. So they practice. And practice. Lenny doesn't give up. And it pays off. Lenny makes a game-changing catch! Now he's proven he can be great some of the time. Which, according to the facts, makes him just like the greatest Hall of Famers, right?"--